Ibadah Sakral Berdasarkan Hati dan Akal:Kajian Teologis Mazmur 100 :1-5 - Panuel Yabes; Paulus Dimas Prabowo (Hymnos: Jurnal Teologi dan Keagamaan Kristen, 2024)
This study discusses the understanding of sacred worship that involves both heart and mind, highlighting the fallacy of the view that true worship is only determined by liturgy. The author argues that finite humans cannot establish the qualifications of true worship to God, and to respond to this, the author analyzes Psalm 100:1-5 using qualitative research methods and the hermeneutics of Old Testament poetry. The five practical steps in the analysis, called the 5T formula, include finding parallelism, determining the poetic structure, tracing figurative language, reviewing the historical background, and finding theological themes. Through this study, the author aims to provide a more appropriate perspective on sacred worship that should involve both the heart and the mind. Looking at the context of Psalm 100:1-5 has given a clear picture of sacred worship, which includes: the right attitude of heart, the right action in worship, and the right reason for worship.